PENGARUH SOSIALISASI, INSENTIF DAN SANKSI PAJAK TERHADAP KEPATUHAN DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KELURAHAN CIPUTAT - Tri Wulan Septiyani; Benarda (Jurnal Nusa Akuntansi, 2025)
This research aims to determine the influence of socialization, incentives and tax sanctions on compliance in paying land and building taxes in Ciputat sub- district. This research uses quantitative methods with a population of 18,491 registered taxpayers in Ciputat Village. With a sampling technique of 400 respondents. This data analysis technique used descriptive statistical tests and hypothesis testing using SPSS version 25. The results of the tax socialization research show that it partially has an influence on compliance in paying land and building taxes. Tax incentives do not have a partial influence on compliance in paying land and building taxes. Tax sanctions show that they have a partial influence on compliance in paying land and building taxes and the research results simultaneously show that socialization variables, incentives and tax sanctions influence compliance in paying land and building taxes.